ANALISIS BANTUAN RENOVASI UNTUK PENGEMBANGAN OBJEK WISATA PEMANDIAN AIR PANAS HJ. HUSNA LUBIS DI SIANCING LUMBAN DOLOK, SIABU, MANDAILING NATAL - Hamonangan (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This study aims to analyze the impact of renovation assistance on the development of the Hj. Husna Lubis Hot Spring Tourist Attraction in Siancing Lumban Dolok, Siabu, Mandailing Natal. The focus of this research is to assess the effectiveness of renovation assistance, which includes the construction of public facilities such as restrooms, parking areas, and road improvements, in increasing the number of visitors and its impact on the local community's economy. The research used a qualitative approach with a descriptive design. Data collection was carried out through interviews with the tourist attraction managers, local communities, and tourists, as well as field observations. Secondary data were obtained from the Mandailing Natal Bappeda reports regarding regional tourism development. The results of the study show that the renovation of facilities at the Hj. Husna Lubis Hot Spring successfully enhanced visitor comfort and prolonged their stay. Furthermore, there was an increase in economic activity around the tourist attraction, such as the opening of new business opportunities for the local community. However, the main challenge found was the lack of effective promotion, which has led to a limited number of tourists from outside the region visiting this tourist attraction. Issues regarding cleanliness and environmental management also need improvement to ensure the sustainability of the tourism site. Nevertheless, the renovation assistance has provided significant positive impacts, both in terms of facility quality and local economic empowerment. This study concludes that although the renovation has increased the tourist attraction's appeal, more structured management in terms of promotion, cleanliness, and community empowerment is essential to ensure sustainable development. With a more comprehensive plan, the Hj. Husna Lubis Hot Spring has the potential to become a leading tourist destination in Mandailing Natal Regency.